2012
DOI: 10.1111/j.1708-8208.2010.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Local Melatonin Application on Implant Osseointegration

Abstract: Within the limitation of this animal study, local melatonin application at the time of implant placement might induce more trabecular bone at implant contact and higher trabecular area density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
65
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 21 publications
6
65
0
1
Order By: Relevance
“…The histopathologic and histomorphometrical analyses for the BIC were performed with an image analyzer (Olympus). The BIC was defined directly from the bone connection with the implant perimeter13. The BIC was measured as the bone implant contact in the cortical and trabecular bone layers following a reported method13.…”
Section: Methodsmentioning
confidence: 99%
“…The histopathologic and histomorphometrical analyses for the BIC were performed with an image analyzer (Olympus). The BIC was defined directly from the bone connection with the implant perimeter13. The BIC was measured as the bone implant contact in the cortical and trabecular bone layers following a reported method13.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that the utilization of these factors improves osseous healing in animal models. 5,7 Their good performance in osseointegration in unloaded implants has been reported. 16 Implants used in other studies were either in the form of sheets or root-form implants of experimental sizes.…”
Section: Discussionmentioning
confidence: 97%
“…Four international units of recombinant human GH in the form of lyophilized powder was used locally in this study and applied as 1 shot around the implant side as stated previously by Tresguerres et al 7,14,15 in 3 different studies. Recombinant human GH is therapeutically equivalent to pituitaryderived human GH in clinical testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations